Retrospective Analysis of the Timing of Radiotherapy Intervention After Induction Chemoimmunotherapy in Unresectable Locally Advanced Lung Squamous Cell Carcinoma - Zeng L; Zhang Y; Zeng A; Ma D (Cancer Management and Research)
Li Zeng, Yu Zhang, Aiju Zeng, Daiyuan Ma Department of Oncology, Affiliated Hospital of North Sichuan Medical College, Nanchong, Sichuan, People’s Republic of ChinaCorrespondence: Daiyuan Ma, Email mdylx@163.comBackground: The optimal combination of immune checkpoint inhibitors (ICIs), radiotherapy, and chemotherapy for unresectable locally advanced lung squamous cell carcinoma (LA-LUSC) remains undefined. This study evaluated induction chemoimmunotherapy followed by radiotherapy ± consolidation ICI in unresectable LA-LUSC, specifically exploring radiotherapy timing impact.Methods: We retrospectively analyzed 54 unresectable LA-LUSC patients receiving induction chemoimmunotherapy followed by radiotherapy. Patients were grouped by radiotherapy timing: Early (after 2– 3 induction cycles, n = 18) and Late (after 4– 6 cycles, n = 36). Survival analysis (Kaplan–Meier, Log-rank) compared progression-free survival (PFS), local PFS (LPFS), distant metastasis-free survival (DMFS), overall survival (OS), and safety. Prognostic factors for PFS/OS were explored.Results: Median follow-up was 30.7 months. Median PFS for all patients was 21.9 months. Early radiotherapy improved PFS (HR = 0.43, p = 0.024) and LPFS (HR = 0.36, p = 0.038). Radiotherapy after 2– 3 induction cycles was an independent predictor of improved PFS (p = 0.040). Overall treatment tolerance was good; grade ≥ 3 pneumonitis incidence was 5.56%. After propensity score matching, OS was significantly longer in patients receiving induction plus consolidation ICI versus induction ICI alone (HR = 0.51, p = 0.038).Conclusion: Induction chemoimmunotherapy followed by radiotherapy demonstrates promising efficacy and manageable toxicity in unresectable LA-LUSC. Initiating radiotherapy earlier (after 2– 3 induction cycles) improves PFS and LPFS and is an independent favorable prognostic factor. Consolidation ICI after combined chemoimmunotherapy and radiotherapy further extends OS compared to induction ICI alone.Keywords: locally advanced non-small cell lung cancer, immune checkpoint inhibitors, radiotherapy, lung cancer